2016
DOI: 10.1590/1678-457x.0047
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of black bean (Phaseolus vulgaris L.) protein hydrolysates

Abstract: The objective of this work was to study the effect of enzymatic hydrolysis of black bean protein concentrate using different enzymes. Bean proteins were extracted and hydrolyzed over a period of 120 min using the enzymes pepsin or alcalase. The protein hydrolysates' molecular weight was assayed by electrophoresis and the antioxidant activity was evaluated by the capturing methods of free radicals ABTS•+ and DPPH. Electrophoretic results showed that the bands above 50 kDa disappeared, when the beans protein was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Ash content was, however, highest in all forms of white kidney bean (T, I, and H), reaching 5.1, 7.2, and 9.2%, respectively. Evangelho, et al [ 68 ] found that black bean proximate composition was 23.1% protein, 4.3% ash, 1.2% fat, 71.4% of total carbohydrate, and protein isolate was 81.6% protein, and 11.4% carbohydrates. Generally, ash content increased with protein isolation or hydrolysis by Alcalase, but protein content significantly increased by 73–75% in isolate forms (BKI, RKI, and WKI), and slightly decreased in the hydrolysates forms (BKH, RKH, and WKH), probably due to the increments in ash content by 11–21%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ash content was, however, highest in all forms of white kidney bean (T, I, and H), reaching 5.1, 7.2, and 9.2%, respectively. Evangelho, et al [ 68 ] found that black bean proximate composition was 23.1% protein, 4.3% ash, 1.2% fat, 71.4% of total carbohydrate, and protein isolate was 81.6% protein, and 11.4% carbohydrates. Generally, ash content increased with protein isolation or hydrolysis by Alcalase, but protein content significantly increased by 73–75% in isolate forms (BKI, RKI, and WKI), and slightly decreased in the hydrolysates forms (BKH, RKH, and WKH), probably due to the increments in ash content by 11–21%.…”
Section: Resultsmentioning
confidence: 99%
“…A similar reduction in protein content of black bean protein was observed in a previous study after 2 h-Alcalase hydrolysis. These reductions were associated with an increase in the ash content of black bean protein hydrolysates, possibly as a result of supplying inorganic alkali to keep the pH constant during hydrolysis [ 68 ]. A similar reduction in protein content accompanied by an increase in ash content was observed in Alcalase-hydrolyzed chickpea protein [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The digestion conditions and enzyme-specificities are key parameters in protein hydrolysis for determining the peptide-bonds to be cleaved. The resulting hydrolysates exhibit bioactive properties that are related to changes in protein structure, a reduction in molecular mass, and the surface-exposure of both ionizable and hydrophobic groups (Evangelho et al, 2016). With respect to the mechanism of action of antioxidant peptides, several studies demonstrated an ability to inhibit lipid peroxidation, to remove free radicals, to chelate metal ions, and to eliminate ROSs.…”
Section: Introductionmentioning
confidence: 99%
“…This results supports studies which show an inverse correlation between molecular weight and antioxidant activity (ZHAO et al 2012). The effect observed in different legume protein hydrolysates showed considerable antioxidant activity (DO EVANGELHO et al 2016;DURAK et al 2013;ALASHI et al 2014;CARRASCO-CASTILLA et al 2012). Table 2 shows the anti-inflammatory activities of protein isolates obtained at four pH levels (3.0, 4.0, 5.0 and 6.0) and hydrolysates (pH 5).…”
Section: Isolated Ph5mentioning
confidence: 99%